Essays on credit rating announcements - Carvalho, Paulo Viegas de (2015)
This thesis is composed of three separate research papers on credit rating announcements. The first paper, in Chapter 1, addresses the effects of rating announcements issued by Fitch, Moody’s and S&P on the idiosyncratic volatility of a firm’s stock return. Such measure of volatility is quantified both in absolute terms and relative to total firm’s volatility, and the results obtained are in general consistent. The paper documents significant increases in volatility after downgrades, especially multi-agency downgrades, whereas no effect of upgrades is evident. Effects are largest for small and low rated firms. Volatility effects of S&P ratings downgrades are larger than those of other ratings agencies, implying that investors’ reactions depend not only on the type of announcements, but also on the agency making the announcement. The second paper, in Chapter 2, reports systematic evidence on some unintended effects of rating downgrades on future credit defaults. Based on complementary causality methodologies and using an extensive database of long-term corporate obligation ratings issued by Moody’s, S&P and Fitch, from 1990 to 2012, the paper shows that downgrades crossing the threshold between investment grade and speculative grade may cause an increase of at least 3% in the 1-year probability of default. The increase in the probability of default seems to be stronger for deeper rating downgrades. The effect is also likely to be stronger for firms that already have a low initial rating. The third paper, in Chapter 3, focuses on the quasi-regulatory role of credit ratings, which depends on the extent to which ratings are stable and reflect a through-the-cycle credit risk assessment. Introducing a new measure of rating dynamics summarizing all observed rating transitions, the paper examines if corporate ratings from the three major agencies fulfill such requirement. Changes in ratings are found to be greater around recessions, with S&P seeming more sensitive than Moody’s and Fitch to the conditions of the business cycle. Despite this sensitiveness to the business cycle, ratings remain a less volatile, though potentially less accurate, measure of credit risk than accounting-based models of default prediction.